2007
DOI: 10.4269/ajtmh.2007.77.209
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Placental and Cord Blood Malaria Infection and Fetal Malnutrition in an Area of Malaria Holoendemicity

Abstract: The objective of this study was to determine the role of malaria in the etiology of fetal malnutrition in Nigeria. This study took place at the Neonatal and Maternity Units of the Wesley Guild Hospital, Ilesa, Nigeria. This is a prospective study of 304 consecutive, singleton, term live births delivered between January and August 2002. Anthropometric and clinical data were recorded. Fetal malnutrition (FM; failure to acquire adequate quantum of fat and muscle mass during intrauterine growth) was diagnosed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
21
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 14 publications
8
21
1
Order By: Relevance
“…The lower prevalence reported in this study may be due to the effective malaria control measures employed in the population, which include sulphadoxine -pyrimethamine 20 Several studies have shown that parity influences susceptibility to placental malaria with primigravidae being more susceptible compared to multigravidae. 19,24,25 In this study, higher parity did not confer any protection and this was consistent with the observations of Bako et al, 6 SuleOdu et al, 8 and Ofori et al 24 This finding was not surprising as same proportion of women across the various parities (nulliparous, primiparous and multiparous) used ITNs and also had at least 2 doses of IPT.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The lower prevalence reported in this study may be due to the effective malaria control measures employed in the population, which include sulphadoxine -pyrimethamine 20 Several studies have shown that parity influences susceptibility to placental malaria with primigravidae being more susceptible compared to multigravidae. 19,24,25 In this study, higher parity did not confer any protection and this was consistent with the observations of Bako et al, 6 SuleOdu et al, 8 and Ofori et al 24 This finding was not surprising as same proportion of women across the various parities (nulliparous, primiparous and multiparous) used ITNs and also had at least 2 doses of IPT.…”
Section: Discussionsupporting
confidence: 81%
“…18 Higher rates of 33.2% and 53.6% were previously reported by Adebami et al 19 and BouyouAkotet et al 20 in Ile -Ife, Nigeria and Gabon respectively. The lower prevalence reported in this study may be due to the effective malaria control measures employed in the population, which include sulphadoxine -pyrimethamine 20 Several studies have shown that parity influences susceptibility to placental malaria with primigravidae being more susceptible compared to multigravidae.…”
Section: Discussionsupporting
confidence: 62%
“…Weight of fetuses was significantly different between the control group and treatment group, this was supported by many previous studies [6,9,10]. The means of birth weight, chest circumference, ponder index, and placental weight were significantly lower among the babies of mothers with malaria-infected placenta than those without.…”
Section: Correlation Test Between Fibrin Deposit and Fetal Weightsupporting
confidence: 75%
“…Fibrin deposit in the treatment group was significantly increasing than the control group in this study. This finding was supported by [9] that histological sections for placental fibrin revealed that women with placental malaria had more deposition than normal pregnant women, although the difference was subtle. Placental malaria induces dysregulated hemostasis both active coagulation and suppressed fibrinolysis and thus provided an expanded functional explanation for the excessive fibrin accumulation found in the infected placenta [9].…”
Section: Correlation Test Between Fibrin Deposit and Fetal Weightsupporting
confidence: 74%
“…16 It seems remarkable that a single dose of S/P during pregnancy could significantly improve the health of the newborn, and that these effects should only be seen in first-born children. It is no less surprising that this drug, even at multiple doses, should demonstrate a virtual absence of benefit in children born of multigravid mothers.…”
Section: Discussionmentioning
confidence: 99%